Pemanfaatan Aplikasi E-Commerce Pada Pemasaran Produk UMKM Keripik Beras Di Desa Kalumpang - Gagah Dwiki Putra Aryono (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
MSMEs are trading businesses managed by business entities or individuals which refer to productive economic businesses in accordance with the criteria stipulated by Law Number 20 of 2008. One of the MSMEs in the Kalumpang Village area is the Rice Chips MSME which is located at Kp Kedung Bulus, Kalumpang Village Padarincang District, Serang Regency, which is a community business in the village. So far, the marketing process for this product is still carried out traditionally, so that sales results are not optimal and the reach of promotion is limited because promotion is still carried out by word of mouth. Therefore, we as students with this community service activity contribute to designing applications and utilizing e-commerce through creating applications or websites as promotional and sales media for Rice Chips products so that we can increase sales and expand market share.